BaCaLu2F10:Ln3+ (Ln = Eu, Dy, Tb, Sm, Yb/Er, Yb/Ho) spheres: ionic liquid-based synthesis and luminescence properties. Issue 40 (18th September 2018) - Liu, Wei; Sun, Qi; Yan, Ming; Song, Yanhua; Zhou, Xiuqing; Sheng, Ye; Zheng, Keyan; Zou, Haifeng
Abstract : Alkaline earth metal rare earth fluoride BaCaLu2 F10 :Ln 3+ (Ln = Eu, Dy, Tb, Sm, Yb/Er, Yb/Ho) submicrospheres with uniform morphology and size were synthesized via a facile ionic liquid-based hydrothermal route. The down- and up-conversion luminescence has been investigated. Abstract : Alkaline earth metal rare earth fluoride BaCaLu2 F10 :Ln 3+ (Ln = Eu, Dy, Tb, Sm, Yb/Er, Yb/Ho) submicrospheres with uniform morphology and size were synthesized via a facile ionic liquid-based hydrothermal route. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and photoluminescence (PL) spectroscopy were used to characterize the samples. The effect of synthetic conditions such as solvent amount, pH, reaction temperature and time on the morphology and size of the final materials was investigated, and a formation mechanism was proposed. The ultraviolet-to-visible down-conversion luminescence of BaCaLu2 F10 :Ln 3+ (Ln = Eu, Dy, Tb, Sm), the up-conversion luminescence of BaCaLu2 F10 : Ln 3+ (Ln = Yb/Er, Yb/Ho), and also the doping site were studied. It was demonstrated that BaCaLu2 F10 was suitable for being utilized as a luminescent host matrix.